Behavior of Concrete Filled Elliptical Steel Tubular Deep Beam under Bending-Shear. (May 2017) - Uenaka, Kojiro; Tsunokake, Hisao
Abstract: A concrete filled elliptical steel tubular, abbreviated as CFEST, member consists of an elliptical hollow steel tube and in-filled concrete. The CFEST member is a family of concrete filled steel tubular (CFT) member having large deformability and toughness due to the confinement effect between the steel tube and the in-filled concrete. When the CFEST member is applied to bridge piers in the river, reduction of the bottom scouring due to the water flow can be expected. The present study aims to investigate, experimentally, the bending shear characteristics of CFEST deep beams through asymmetric four-point loading test method. The selected testing parameters are diameter-to-thickness ratio and two loading directions, namely the major and the minor axes. The results showed that shear capacity of CFEST members is strongly affected by the diameter-to-thickness ratio. The observed failure modes were cracking of the tube and/or shear failure of the in-filled concrete. A method to predict simple shear capacity of the CFEST deep beam is mainly discussed. Additionally, elasto-plastic principal stress behavior of the steel tube is also mentioned.